Developing a Multi-Dimensional Service Experience Model for Halal Food Resturants / Voon Boo Ho … [et.al.]. - Voon, Boo Ho; Harrisson Tama, Muhammad Harrizz; Suhaimi, Rosita (2013)
A customer's personal effect and/or emotional experience of a service could play a greater role than any other factors in ensuring business success in this ever competitive business environment (Kim, Cha, Knutson and Beck, 2011). A satisfactory and positive personal experience with a service-based transaction (e.g. foodservice) may lead to repeat purchases from the same vendor (McKenzie, 2000). In fact, every stage of a service delivery should provide authentic experiences. Gilmore and Pine (2007) hinted that the experience authenticity is crucial for effective management. They argued that such a unique experience, authenticity, should be the primary source of differentiation, which is the real value demanded by the customers. Customer experience has been regarded as an useful marketing tool as well as a way to gain superior service performance (e.g. Kim et al., 2011; Kim and Moon, 2009; Qu, 1997; Woo et al., 2009; Wong, 2004). Nevertheless, there has been scant attention and even less emphasis on an empirical research to investigate the emotional service experience and quality practices of the priority service sector such as Halal foodservice. The customer emotional experience and service practices of the Halal restaurants or food establishments need to be understood and measured for effective and efficient management of the Halal foodservice to benefit the public especially the Muslim customers.